2017
DOI: 10.1002/ece3.3247
|View full text |Cite
|
Sign up to set email alerts
|

Predators do not spill over from forest fragments to maize fields in a landscape mosaic in central Argentina

Abstract: South America is undergoing a rapid and large‐scale conversion of natural habitats to cultivated land. Ecosystem services still remain important but their level and sustainability are not known. We quantified predation intensity in an Argentinian agricultural landscape containing remnants of the original chaco serrano forest using artificial sentinel prey. We sought to identify the main predators and the effect of landscape configuration and maize phenology on predation pressure by invertebrate and vertebrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 72 publications
(100 reference statements)
3
15
0
Order By: Relevance
“…However, our results showed that the abundance of predatory and omnivorous ground beetles was not higher at forest borders under ag-ricultural influence compared to the forest interiors, assuming that dispersal or spillover of these beetles into neighbouring agricultural field is limited. In correspondence with our assumption, a recent study, using artificial sentinel prey, also indicated little of predator spillover from the native forest remnants to the cultivated matrix in Argentina (Ferrante et al 2017). It seems that the repeated anthropogenic interventions could have negative effect on ecosystem functions at edges, with negative consequences for ecosystem services like pest control.…”
Section: Discussionsupporting
confidence: 84%
“…However, our results showed that the abundance of predatory and omnivorous ground beetles was not higher at forest borders under ag-ricultural influence compared to the forest interiors, assuming that dispersal or spillover of these beetles into neighbouring agricultural field is limited. In correspondence with our assumption, a recent study, using artificial sentinel prey, also indicated little of predator spillover from the native forest remnants to the cultivated matrix in Argentina (Ferrante et al 2017). It seems that the repeated anthropogenic interventions could have negative effect on ecosystem functions at edges, with negative consequences for ecosystem services like pest control.…”
Section: Discussionsupporting
confidence: 84%
“…This has been found over a number of case studies in a review by Samu et al (1999). Predation pressure experiments also indicated a lack of spillover of predators between forested habitats and corn fields (Ferrante et al 2017). Areal woody elements in the present study were plantations, without exemption.…”
Section: Discussionsupporting
confidence: 50%
“…For natural enemies that rely only on resources within farm fields, proximity to seminatural habitats can be irrelevant [40] or even detrimental. For example, pests in sun-grown Brazilian coffee were suppressed by ants adapted to open habitats and, in this case, pest suppression increased at greater distances from forest fragments [41].…”
Section: Connectivitymentioning
confidence: 99%
“…For example, we note that, while six studies documented correlations between natural enemy and pest density (arrow i), without an experimental approach, the relative strengths of landscape predictors and numeric responses between enemies and prey are unknown. Based on [37][38][39][40][41][42][43][44][45]51,74]. millennia, and change relatively slowly.…”
Section: Figure 2 Viewing Pest Suppression Through the Lens Of Multimentioning
confidence: 99%